A New Trophic State Index for Lagoons. (9th March 2014) - Gupta, Mukesh
Abstract : This paper proposes a new nitrogen-based trophic state index (TSI) for the estimation of status of eutrophication in a lagoon system. Nitrite-nitrogen (NO2 -N) is preferable because of its greater abundance in Chilika lagoon and its relation to other criteria of trophic state, for example, chlorophyll-a (Chl- a ) and Secchi disk depth (SDD). Nitrite is preferable over nitrate because the former decreases the fluorescence and affects photosynthesis, thereby controlling primary production. This paper also computes TSI using Chl- a and SDD. The three parameters account for the biological, chemical, and physical characteristics of the lagoon. It will be possible to estimate the TSI of freshwater and brackish water lagoons and other water bodies using the new expressions taking into consideration the spatial and temporal variability in the dataset. Depending on the data availability, alternative TSI (Chl- a ) and TSI (SDD) can account for the biological and physical contributions to eutrophication. The estimated TSI can account for Chl- a and NO2 -N up to 322.18 mg m −3 and 61.99  μ g L −1, respectively. The TSI based on these three parameters can serve as a complimentary and predictive tool for lagoon management and field programs to monitor the health of a lagoon.